Critical role of ROCK2 activity in facilitating mucosal CD4+ T cell activation in inflammatory bowel disease. (May 2018) - Yang, Wenjing; Zhou, Guangxi; Yu, Tianming; Chen, Liang; Yu, Lin; Guo, Yanmin; Cong, Yingzi; Liu, Zhanju
Abstract: Rho-associated kinase (ROCK) has been found to be involved in the pathogenesis of a variety of autoimmune diseases, but the role of ROCK in inflammatory bowel disease (IBD) is still elusive. In this study, we demonstrated that the levels of ROCK2, but not ROCK1, activity were significantly upregulated in peripheral blood mononuclear cells (PBMC) and inflamed mucosa from IBD patients using a ROCK activity assay, and that ROCK2 activity in intestinal mucosa was positively correlated with disease severity. Stimulation with TNF markedly upregulated ROCK2 activity in IBD CD4 + T cells through NF-κB signaling. Blockade of ROCK2 activity using Slx-2119 significantly suppressed proinflammatory cytokines in inflamed mucosa from IBD patients including IFX-unresponsive CD patients, and inhibited IBD CD4 + T cells to differentiate into Th1 and Th17 cells through downregulating phosphorylated Stat1 and Stat3, but promoted Treg cell differentiation through upregulating phosphorylated Stat5. Furthermore, oral administration of Slx-2119 markedly ameliorated intestinal mucosal inflammation in TNBS-induced colitis in mice and decreased proinflammatory cytokines productions in inflamed colon. Our data indicate that ROCK2 plays a critical role in inducing mucosal T cell activation and inflammatory responses in IBD and that inhibition of ROCK2 activity might serve as a novel therapeutic approach in the management of IBD. Highlights: ROCK2 activity is increased in inflamed mucosa and PBMC of IBD patients. Blocking ROCK2 decreases proinflammtory cytokines in IFX-unresponsive CD patients, and regulates CD4 + T cell differentiation. ROCK2 selective inhibitor, Slx-2119, ameliorates an experimental colitis in mice induced by TNBS. This study highlights the vital role of ROCK2 in the pathogenesis of IBD, and provide a potential therapy for IBD.